Evaluation of viral concentration methods from irrigation and processing water - De Keuckelaere, Ann; Baert, Leen; Duarte, Alexandra; Stals, Ambroos; Uyttendaele, Mieke (Journal of virological methods, 2013)
► We compared four viral concentration methods for their recovery in water. ► MNV-1 and MS2 phages were used as surrogate viruses during this study. ► All methods were evaluated in processing water and four types of irrigation water. ► The best method used a negatively charged membrane with the Tr alk elution buffer. ► The best method was tested for its recovery of HAV, GI and GII NoV and RV. Four viral concentration methods were evaluated for their efficiency in recovering murine norovirus-1 (MNV-1) (surrogate for human noroviruses (NoV)) and MS2 bacteriophages from processing water (1L) and four different types of irrigation water (bore hole water, rain water, open well and river water) (2–5L). Three methods were based on the viral adsorption and elution principle, two methods using an electronegative HA-membrane (Katayama et al., 2002), one method using an electropositive Zetapor membrane according to CEN/TC275/WG6/TAG4 and the fourth method was based on size exclusion using a tangential flow filtration system. Detection of MNV-1 was achieved by real-time RT-PCR and detection of MS2 by double-layer plaque assay. For the recovery of MNV-1, the method using an electronegative HA-filter in combination with an elution buffer earlier optimized by Hamza et al. (2009) (Method 1) performed best for all types of water (recovery: 5.8–21.9%). In case of MS2 detection, the best method depended upon the type of water although Method 1 provided the most consistent recovery. To complete this evaluation, the Method 1 was evaluated further for the concentration of human enteric viruses (GI and GII NoV, hepatitis A virus (HAV) and rotaviruses) in the same five types of water. Although detection of rotaviruses (RV) was somewhat less efficient, Method 1 proved reliable for the detection of NoV and HAV in all water types. Mean recovery efficiencies ranging from 4.8% for detection of GI NoV in open well water to 32.1% for detection of HAV in bore hole water, depending on the water type and the viral pathogen analyzed.